ChemInform Abstract: Color‐Tunable and White Luminescence Properties via Energy Transfer in Single‐Phase KNaCa2(PO4)2:A (A: Ce3+, Eu2+, Tb3+, Mn2+, Sm3+) Phosphors. Issue 6 (11th February 2014) - Geng, Dongling; Shang, Mengmeng; Zhang, Yang; Lian, Hongzhou; Lin, Jun
Abstract The title phosphors are synthesized by a Pechini‐type sol—gel method followed by calcination in air at 950 °C for 4 h.